Determinants of Medication Adherence in Hypertension Patients in Level I Health Facilities in Kembaran District - Silma Kaaffah; Galih Samodra; Yulinda Eka Pratiwi (Viva Medika, 2024)
Medication adherence is the key to controlling blood pressure in hypertensive patients to minimize the risk of complications. The research aims to assess level of medication adherence and identify influencing factors. The quasi-experimental research method used purposive sampling to create a control group and 2 intervention groups (pill box and medication chart) with each group 30 patients. Prospective data collection with pre-post design (week-1 and week-4) as well as observing clinical data on blood pressure, medication adherence. Questionnaire of medication non-adherence determinants was taken at week 4. The questionnaire instrument was validated with Cronbach Alpha reliability >0.06. The results of the statistical analysis were significant (p-value <0.05) with increasing the mean score of medication adherence in the pill box was 1.2 and the medication chart was 0.7. The reduction in systolic blood pressure in the intervention group was significant (p-value <0.05) by more than 2 mmHg. A total of 35.6% of patients were reluctant to ask health workers for medication information and 45.6% needed someone to remind them to take medication. In conclusion, increasing medication adherence and reducing blood pressure can be achieved with intervention and requires social support from family and health-care professional.